Efektivitas Penerapan Aplikasi Jakarta Evolution (Jakevo) Dalam Pelayanan Terpadu Satu Pintu (Studi Pelayanan Perizinan Di Kelurahan Semper Timur Jakarta Utara) - Amalia Amanda; Tri Ubayanto; Totok Priyono (Jurnal Ilmu Administrasi Publik, 2023)
JAKEVO is an application launched in 2018 by the provincial government of DKI Jakarta as a form of innovation in the field of digitizing public services previously according to PERMENDAGRI number 138 of 2017 concerning the implementation of one-stopRegional Services   which   reads   ’electronic   services hereinafter abbreviated as PSE, are licensing and non-licensing services provided through PTSP electronically, hereinafter referred to as PTSP-el.’. After 5 (five) years, JAKEVO is now used by the entire community to apply for licensing and non-licensing online, where now DKI Jakarta DPMPTSP officers can perform community services from anywhere online during working hours. In this study, the researchers used the theory of effectiveness from Campbell (1989) to explain the effectiveness of the application of Jakarta   Evolution   application in   one-stop integrated service study of licensing services in Semper Timur Village, North Jakarta, Campbell measured the success of the program based on 5 (five) dimensions, namely, Program success, Target Success, Input and Output levels, satisfaction with the overall goal achievement Fund Program. The research method used in this study is a qualitative descriptive method, with data collection techniques using interviews,observation and documentation. The success of the JAKEVO service program was evaluated by considering the scope of services provided to dynamic residents, the ease for residents to operate JAKEVO when applying for services, the certainty of services obtained by notification from PTSP, and the ease of JAKEVO at the same time being accessed by residents. JAKEVO is an application that makes it easier for citizens, efficient in time, can overcome extortion, increase transparency in licensing services and is effective for use by the community because everything is done online, which is the goal for the success of the target on digitizing   services.   However,   the   community   does   not   get socialization on how to use JAKEVO, so JAKEVO usage assistance is carried out for people who come to East Semper village PTSP and the existence of a Whatsapp number as a customer contact to receive facilities and complaints from residents. JAKEVO application provides a comment and rating field for users to provide comments and feedback regarding their experience using the JAKEVO application, as well as features for applying for permits and non-permits by the community, and the process at PTSP, and residents receive results, which is the process of input and output level of the JAKEVO application. Satisfaction with the program is explained by the availability of JAKEVO usage flow including account creation, document upload to the JAKEVO   system,   document   completeness   check,   document verification, and issuance of license letters, as well as document submission to residents through JAKEVO and the existence of obstacles in the use of JAKEVO is a rather difficult server to be accessed at the same time by residents JAKEVO is an application launched in 2018 by the provincial government of DKI Jakarta as a form of innovation in the field of digitizing public services previously according to PERMENDAGRI number 138 of 2017 concerning the implementation of one-stopRegional Services   which   reads   ’electronic   services,   hereinafter abbreviated as PSE, are licensing and non-licensing services provided through PTSP electronically, hereinafter referred to as PTSP-el.’. After 5 (five) years, JAKEVO is now used by the entire community to apply for licensing and non-licensing online, where now DKI Jakarta DPMPTSP officers can perform community services from anywhere online during working hours. In this study, the researchers used the theory of effectiveness from Campbell (1989) to explain the effectiveness of the application of Jakarta   Evolution   application in   one-stop integrated service study of licensing services in Semper Timur Village, North Jakarta, Campbell measured the success of the program based on 5 (five) dimensions, namely, Program success, Target Success, Input and Output levels, satisfaction with the overall goal achievement Fund Program. The research method used in this study is a qualitative descriptive method, with data collection techniques using interviews,observation and documentation. The success of the JAKEVO service program was evaluated by considering the scope of services provided to dynamic residents, the ease for residents to operate JAKEVO when applying for services, the certainty of services obtained by notification from PTSP, and the ease of JAKEVO at the same time being accessed by residents. JAKEVO is an application that makes it easier for citizens, efficient in time, can overcome extortion, increase transparency in licensing services and is effective for use by the community because everything is done online, which is the goal for the success of the target on digitizing   services.   However,   the   community   does   not   get socialization on how to use JAKEVO, so JAKEVO usage assistance is carried out for people who come to East Semper village PTSP and the existence of a Whatsapp number as a customer contact to receive facilities and complaints from residents. JAKEVO application provides a comment and rating field for users to provide comments and feedback regarding their experience using the JAKEVO application, as well as features for applying for permits and non-permits by the community, and the process at PTSP, and residents receive results, which is the process of input and output level of the JAKEVO application. Satisfaction with the program is explained by the availability of JAKEVO usage flow including account creation, document upload to the JAKEVO   system,   document   completeness   check,   document verification, and issuance of license letters, as well as document submission to residents through JAKEVO and the existence of obstacles in the use of JAKEVO is a rather difficult server to be accessed at the same time by residents.